Unraveling Contradictions in Quality Management Implementation: An Empirical Study of TQM and ISO Certification in SMEs: JEL Classification: L15, L25, L60, M11, M21, O14, O33, O53, C38 - Najamuddin, Mahfud Nur; Ramlawati, Ramlawati; Nursiany, Nursiany (Newinera Publisher, 2025)
In an environment marked by escalating competition, critical customer scrutiny, and evolving supply chain expectations, quality management has become indispensable, particularly for small and medium-sized enterprises (SMEs). A review of existing literature reveals that adopting formal systems like Total Quality Management (TQM) and ISO certification often fails to yield significant performance benefits. This study therefore probes a more fundamental issue: to what extent is quality performance driven by the mere existence of these systems versus their level of implementation within managerial processes? Drawing on empirical research involving 120 manufacturing SMEs in Makassar City, analyzed through structural equation modelling (SEM), this paper investigates the interdependencies among top management support, infrastructure, stakeholder participation, process management, and quality performance. Findings indicate that only process management exerts a direct influence on quality performance, while leadership, infrastructure, and stakeholder involvement exert indirect, residual effects constrained by how quality processes are configured. Consequently, this study posits that SMEs should embed quality as an integral, internalized practice, rigorously implement it, and continually pursue improvements. High performance in these firms appears less contingent on external certification or formal policy adoption and more on the strategic integration of quality within their process systems and routines. This insight underscores the need for SMEs to shift focus from compliance-driven approaches to cultivating deeply ingrained quality-centric operational cultures, thereby ensuring sustained competitive advantage and responsiveness to dynamic market demands.